Development of Student Worksheet Assisted by Stellarium Website Through Design-Thinking Framework - Rahadi Santoso; Samsudin, Achmad; Sinaga, Parlindungan; Kohar, Engkoh Saepul (Indonesian Journal of Mathematics and Natural Science Education, 2024)
The purpose of this study is to develop a student worksheet assisted by Stellarium website through a design-thinking framework on the topic of the solar system which is stated to be theoretically feasible based on_validation results by the experts. The development of this student worksheet was carried out because students in seventh grade at one of the State Middle Schools in Bandung experienced obstacles in completing the student worksheet due to lack of time and feel less understanding of the material contained in the student worksheet. This study uses the Design & Development Research with a design-thinking framework consisting of 5 principles, namely empathize, define, ideate, prototype, and test. The initial stage was conducting interviews with 15 students, identifying problems in seventh grade, then making a prototype in the form of student worksheet and validated by experts. Findings indicate that the average overall percentage of validation is 91.9% which means that the student worksheet is included in the very good category, This data also shows that the student worksheet is worthy of being tested in schools with improvements according to the suggestions and input given. However, this student worksheet has not been tested yet, due to limited time, so a trial process needs to be conducted in improving conceptual understanding, increasing interest in learning and developing 21st century skills.